Upaya Peningkatan Keaktifan Belajar Siswa Kelas 4 Tema 8 Menggunakan Model Student Team Achievement Division - Suhariyadi, Suhariyadi; Eko, Sugeng; Suyoto, Suyoto (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2023)
This study aims to determine whether the STAD model can increase student activeness. This study used Classroom Action Research (PTK) which consisted of two cycles. Each cycle consists of two meetings. The subjects in the study were grade IV students of SDN Karanggedang totaling 11 students consisting of 9 boys and 2 girls. The data collection methods used were interviews, observation and documentation. STAD (Student Team Achievement Division) model